A Comparative Study of Active Queue Management Algorithms for Network Performance Evaluation - Ammar Hameed Shnain; Sarah Hadi Shaheed (International Journal of Supply Chain Management, 2018)
With the current advances in network activities, there appears to be wide needs for Quality of Services (QoS) and fairness among flows. As such, the links are also forced as a result in order to effectively perform in congestion control and avoidance. For this reason, active queue management algorithms were proposed in order to handle QoS issues. This study will examine the unique the performance effeteness of three AQM algorithms namely REM, AQV, and CoDel due to the little evidence found in literature about their performance. The performance above mentioned algorithms will be evaluate via simulation tool (NS2) in terms of response time, throughput and packet loss in single link network . The throughput result showed that REM performed best, closely followed by CoDel and AVQ. REM has the faster response time, followed by CoDel , with AVQ performing worst overall by a significant margin. the packet loss showed AVQ, and CoDel algorithms to do equally, and seem REM performs very poorly. The performance result of REM, AVQ, and CoDel showed different performance results in which REM and CoDel mechanisms helped control the amount of bandwidth shared within a network.